Relationship between Metabolic Syndrome and Ocular Microcirculation Shown by Laser Speckle Flowgraphy in a Hospital Setting Devoted to Sleep Apnea Syndrome Diagnostics - Tomoaki Shiba; Mao Takahashi; Tadashi Matsumoto; Yuichi Hori (Journal of Diabetes Research)
Purpose. To clarify whether the incidence of metabolic syndrome (MetS) and the overlap of MetS components are affecting the ocular circulation shown by laser speckle flowgraphy (LSFG). Materials and Methods. We studied 76 consistent patients. Blowout score (BOS) and blowout time (BOT), which are the pulse waveform analysis parameters, and mean blur rate (MBR) using LSFG in the optic nerve head (ONH) and choroid were evaluated. Throughout, the ONH was separated out from the vessels and tissue for analysis and MBRs in the ONH were divided into four sections (superior, temporal, inferior, and nasal). Results. Thirty-two patients were diagnosed having Mets. MBR-Tissue (P=0.003), MBR-All (P=0.01), MBR-Choroid (P=0.04), and BOS-Choroid (P=0.03) were significantly lower in patients with MetS than in the patients without MetS. Multiple-regression analysis revealed the temporal side of MBR-Tissue and BOS-Choroid which were identified as factors contributing independently to the overlap of the MetS components. Multiple-regression analysis also revealed that the MetS components were identified to be factors independently contributing to the BOS-Choroid and temporal side of MBR-Tissue. Conclusion. Our study clarified that the incidence of MetS and the overlap of the MetS components are significantly affecting the ONH and choroidal microcirculation.